2008
DOI: 10.3934/dcdsb.2008.10.925
|View full text |Cite
|
Sign up to set email alerts
|

Control for fast and stable Laminar-to-High-Reynolds-Numbers transfer in a 2D Navier-Stokes channel flow

Abstract: Abstract. We consider the problem of generating and tracking a trajectory between two arbitrary parabolic profiles of a periodic 2D channel flow, which is linearly unstable for high Reynolds numbers. Also known as the Poiseuille flow, this problem is frequently cited as a paradigm for transition to turbulence. Our procedure consists in generating an exact trajectory of the nonlinear system that approaches exponentially the objective profile. Using a backstepping method, we then design boundary control laws gua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…For n = 0, the result follows from (A. 33). Assume that the bound is correct for all i in ∆F n (x, ξ).…”
Section: )mentioning
confidence: 92%
See 1 more Smart Citation
“…For n = 0, the result follows from (A. 33). Assume that the bound is correct for all i in ∆F n (x, ξ).…”
Section: )mentioning
confidence: 92%
“…By the assumptions on the coefficients and applying Theorem A.2, the direct and inverse transformations (3.23) and (3.38) have kernels that are C 2 (T ) functions. Differentiating twice with respect to x in these transformations, it can be shown that the H 2 norm of γ is equivalent to the H 2 norm of z (see for instance [33]). Thus, if we show H 2 local stability of the origin for (5.15)-(5.18), the same holds for z.…”
Section: Preliminary Definitionsmentioning
confidence: 99%
“…For the determination of the solution k(z, s, t) of (24) using either formal integration and successive approximation or a suitable numerical scheme the reader is referred to, e.g., Meurer and Kugi (2009a); Jadachowski et al (2012). With Assumption 10 it can be shown that k(z, s, t) is a strong solution to (24) Vazquez et al, 2008;Meurer and Kugi, 2009a).…”
Section: Stabilisation Of Tracking Error Dynamicsmentioning
confidence: 99%
“…The boundary stabilization of Navier-Stokes equations, with tangential controllers or normal controllers was studied in two dimensions, for example by Barbu [5,4], Munteanu [13], Coron [17], Krstic [18], [1], [2], Raymond [15]. In most of these papers, either there are sufficiently many boundary controls so there are no missing directions, or stabilizability is proved but with no specific decay rate (except in [15]).…”
Section: ∂U ∂Tmentioning
confidence: 99%